1995
DOI: 10.1016/0378-1097(95)00343-4
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of Acremonium lolii and Acremonium coenophialum endophytes through arbitrarily primed PCR

Abstract: Using a random decamer 5'-CCGAGGTGAC-3' in an arbitrarily primed PCR, similar band patterns were observed between Acremonium lolii and A. coenophialum DNA, which were somewhat different from those formed by other fungal DNA. Despite sharing bands of around 0.7, 0.9 and 2.1 kb, A. lolii can be distinguished from A. coenophialum by the presence of an additional band at around 0.5 kb in the arbitrarily primed PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2000
2000
2000
2000

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…These included OPAA11 (59-ACCCGACCTG-39) [19,20], OPD18 (59-GAGAGCCAAC-39) [20], OPAA17 (59-GAGCCCGACT-39) [21] and OPU15 (59-ACGGGCCAGT-39) [22]. By employing a rapid DNA puri®cation protocol [23] and, more recently, a further improved mini-preparation procedure [24], 230 isolates from 25 dermatophyte species and subspecies (varieties), comprising 16 Trichophyton species and subspecies (varieties), eight Microsporum species and E.¯occosum, were examined with one of these four primers in AP-PCR [19±22] ( Table 1). The results indicated that of the 25 dermatophyte species and subspecies examined, 16 (except between T. equinum var.…”
Section: Ap-pcrmentioning
confidence: 99%
“…These included OPAA11 (59-ACCCGACCTG-39) [19,20], OPD18 (59-GAGAGCCAAC-39) [20], OPAA17 (59-GAGCCCGACT-39) [21] and OPU15 (59-ACGGGCCAGT-39) [22]. By employing a rapid DNA puri®cation protocol [23] and, more recently, a further improved mini-preparation procedure [24], 230 isolates from 25 dermatophyte species and subspecies (varieties), comprising 16 Trichophyton species and subspecies (varieties), eight Microsporum species and E.¯occosum, were examined with one of these four primers in AP-PCR [19±22] ( Table 1). The results indicated that of the 25 dermatophyte species and subspecies examined, 16 (except between T. equinum var.…”
Section: Ap-pcrmentioning
confidence: 99%
“…Desde sua descrição o uso de marcadores RAPD tem tido uma difusão extremamente rápida, sendo extremamente útil para estudos de identificação taxonômica (Liu et al, 1995;Yuan et al, 1995;Guzmán et al,1999), caracterização de raças (Guthrie et al, 1992;Jiménez-Gasco et al, 2001), analise de variabilidade da virulência em fungos fitopatogênicos (Cooke et al, 1996;Fernández & Hanlin, 1996;Mostafa et al, 2002;Araya et al, 2004;Belabid et al, 2004) e variabilidade inter e intraespecífica de populações de diferentes regiões (Liew & Irwin, 1994;Guzmán et al, 1995;Jamil et al, 2000;Roy et al, 2000).…”
Section: Métodos De Controleunclassified